Persepsi Pemilih Milenial Dalam Pemilu Serentak 2019 di Provinsi Daerah Istimewa Yogyakarta - Moch. Edward Trias Pahlevi; Wildhan Khalyubi; Muhammad Iqbal Khatami (Badan Pengawas Pemilihan Umum, 2019)
The 2019 General Elections are legislative elections and presidential elections that are held simultaneously on the same day. This is done by the Constitutional Court Decision Number 14/PUU-X/2013 on the implementation of the elections, which aims for budget efficiency, influencing commitment to strengthen political parties in permanent coalition to strengthen their power base in state institutions, and also strengthen the presidential system. This research examines the issue of millennial voter generation in the 2019 simultaneous general election. This research use qualitative research methods. The findings of this research are: (1) Millennial generation in the Special Region of Yogyakarta said that most of them get electoral information through social media, (2) The underlying factor for millennial voters came to the polls, which was to realize the election as an important means for democracy, (3) Millennial voters said they have problems, namely confusion in determine their choice at the polling station due to the many candidates who are the effects of the simultaneous election of 5 ballots, (4) Millennial generation admit find the practice of money politics and regard money politics as a matter of course.